2019
DOI: 10.1108/edi-02-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

The work-life experiences of an invisible workforce

Abstract: Purpose The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The keyword-search term identified and selected in this paper included "work-life balance", instead of any other related keywords. WLB is an emerging concept that researchers use to de-gender debates about the work-life imbalance and emphasize a broader and more inclusive approach (Akanji et al, 2020a, b;Au et al, 2020). From the existing literature studies, we identified that this term is entirely different from other closely associated terms such as WFC, WFE and WFB.…”
Section: Search Stringmentioning
confidence: 99%
See 3 more Smart Citations
“…The keyword-search term identified and selected in this paper included "work-life balance", instead of any other related keywords. WLB is an emerging concept that researchers use to de-gender debates about the work-life imbalance and emphasize a broader and more inclusive approach (Akanji et al, 2020a, b;Au et al, 2020). From the existing literature studies, we identified that this term is entirely different from other closely associated terms such as WFC, WFE and WFB.…”
Section: Search Stringmentioning
confidence: 99%
“…Hence, WLB has become a dynamic phenomenon affecting an individual's perception about work and non-work activities to assess compatibility between both, which can promote growth in accordance with their present life priorities. Most often, studies have confined the notion of WLB with the mere absence of conflict between work and family (Au et al, 2020;Robertson et al, 2019), but in a broader sense, it is a separate and unique construct. WLB reflects the perceptions of striking a balance between employees' work and personal life, including sensitivities about social life and leisure time (Casper et al, 2018;Chan et al, 2020;Weale et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elsewhere, we see that the majority of the work focusing on precarious employment in Malaysia is concerned with the plight of migrant workers, especially those working within the palm oil industry or as domestic workers (Pye et al 2012;Kumar et al 2014;Au et al 2019;Miles et al 2019). With regards to the former, Malaysia's palm oil sector is heavily reliant upon roughly 1 million migrant workers, the majority of whom are from neighbouring Indonesia (Pye et al 2012, p. 330).…”
Section: Literature Reviewmentioning
confidence: 99%